ЖАДИД МАТБУОТИ: МУРАККАБ ДАВРНИНГ ЁРҚИН КЎЗГУСИ - Сувонов, Л. (SCIENCE and SOCIETY, 2021)
This article reflects the political situation at the beginning of the last XX century and its coverage in the press. The author explains his comments about the political developments in Turkestan and around the world at the beginning of the last century, Jadid intelligentsia attitude to these processes, articles’ features published on this topic. A number of newspapers and magazines published in that period, as well as the activities of Jadid enlighteners who actively participated were explained in detail in this research.